The Influence Of Work Discipline, Work Facilities And Work Environment On Employee Work Productivity At The Faculty Of Economics Al-Azhar University Medan - Roma Harahap, Siti (International Journal of Educational Research & Social Sciences, 2025)
At the Faculty of Economics, Al-Azhar University, Medan, this study investigates how work discipline, work environment, and work facilities affect employee work productivity. This study is a quantitative study and uses a total sampling technique. The sample consists of 32 staff members. The Faculty of Economics, Al-Azhar University, Medan found that, partially, work discipline, work facilities, and work environment have a positive and significant effect on employee productivity. On the other hand, work discipline, work facilities, and work environment also have a positive and significant effect on employee productivity.